Pengaruh Digital Leadership, HI-HRMP, dan Employee Dynamic Capabilities terhadap Employee Digital Performance di Sektor Teknologi Informasi - Wilarman, Navisha; Tiarapuspa (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This research examines how Digital Leadership, High-Involvement Human Resource Management Practices (HI-HRMP), and Employee Dynamic Capabilities (EDC) impact Employee Digital Performance (EDP) within Indonesia’s IT industry. Data collected from 329 employees were processed using structural equation modeling. The findings suggest that Digital Leadership has no significant effect on Employee Dynamic Capabilities or Employee Digital Performance. HI-HRMP has a direct influence on Employee Digital Performance, while Employee Dynamic Capabilities notably enhance Employee Digital Performance. These results underscore the essential role of HR practices in boosting digital performance, with an emphasis on strategic interventions.